2012
DOI: 10.1016/j.biosystems.2012.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic fields in embryogenesis, regeneration, and cancer: Non-local control of complex patterning

Abstract: Establishment of shape during embryonic development, and the maintenance of shape against injury or tumorigenesis, requires constant coordination of cell behaviors toward the patterning needs of the host organism. Molecular cell biology and genetics have made great strides in understanding the mechanisms that regulate cell function. However, generalized rational control of shape is still largely beyond our current capabilities. Significant instructive signals function at long range to provide positional inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
178
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 200 publications
(182 citation statements)
references
References 272 publications
(312 reference statements)
1
178
0
3
Order By: Relevance
“…In developmental biology, morphogenetic fields are discrete regions of developing organisms that function as the major units of development (Levin 2012;Gilbert and Barresi 2016). Since the general fate of their cells is genetically determined, changes in these fields bring about evolutionary changes.…”
Section: Introductionmentioning
confidence: 99%
“…In developmental biology, morphogenetic fields are discrete regions of developing organisms that function as the major units of development (Levin 2012;Gilbert and Barresi 2016). Since the general fate of their cells is genetically determined, changes in these fields bring about evolutionary changes.…”
Section: Introductionmentioning
confidence: 99%
“…Mojica et al [19] examined how unicellular organisms, as well as some specialized eukaryotic cells, evolve through a master plan of transformations under Darwinian natural selection from an initial population of cells simulated as Pickover biomorphs. And Levin [15] used biomorphs as an example of emergence of complex morphology from simple low-level rules. In the rest of the paper we present two modifications of the biomorph algorithm which will expand the class of biomorphs.…”
Section: Introductionmentioning
confidence: 99%
“…Bioengineering, inspired by embryology, is now at a point where transforming and creating new tissues from cells is possible. Many active molecules found in cancer are also found in embryos while they develop and it is hoped that in the future, cancer can be re-programmed by chemicals derived from active molecules involved during embryogenesis (Levin, 2012;Mintz and Illmensee, 1975;Schulze, 2012;Spike et al, 2012). Furthermore, it has been suggested that a dynamic change in the interactions between cells and tissues may result in a dysregulation of the body routine.…”
Section: Anomalies and Monstersmentioning
confidence: 99%